2017
DOI: 10.18203/2394-6040.ijcmph20173346
|View full text |Cite
|
Sign up to set email alerts
|

Pre lacteal feeding practice among mothers in a rural area of Karnataka: a cross sectional study

Abstract: INTRODUCTIONColostrum, the early breast milk plays a vital role in boosting the immunity of a newborn.1,2 It also helps in building the precious bond between the mother and the child. Apart from the duration of breast feeding and the time at which a child is weaned, the time of initiation of breast feeding also plays a crucial role in determining the health of child. 3In many countries across the world, the practice of giving new born babies substances other than breast milk is a common cultural practice. 4 Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 5 publications
2
8
1
3
Order By: Relevance
“…Also, a study conducted in eastern Ethiopia was facility-based it is assumed that mothers with good educational status have a high chance of visiting health centers. The finding of this study is also lower than studies carried out in Nepal 26.5%, Vietnam 73.3%, Karnakata, India 32.03%, Egypt 58%, Kampala, Uganda 31.3%, and South Sudan 53% [ 4 , 5 , 19 , 36 38 ]. This difference could be due to the difference in maternal health service utilization between study populations.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Also, a study conducted in eastern Ethiopia was facility-based it is assumed that mothers with good educational status have a high chance of visiting health centers. The finding of this study is also lower than studies carried out in Nepal 26.5%, Vietnam 73.3%, Karnakata, India 32.03%, Egypt 58%, Kampala, Uganda 31.3%, and South Sudan 53% [ 4 , 5 , 19 , 36 38 ]. This difference could be due to the difference in maternal health service utilization between study populations.…”
Section: Discussioncontrasting
confidence: 83%
“…Pre-lacteal food has a great impact on the newborns' mental health, physical development, and fighting against infections [18]. Besides, this feeding process reduces the practice of exclusive breastfeeding, which can be dangerous to the child and results in early cessation of breastfeeding [19]. It is also associated with a more likely chance of dying in the neonatal period [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, sugar water and honey were commonly given as prelactial feeds. Similar findings were found in studies conducted by Srividya et al, Yadavannar et al and Goyle et al 12,16,17 In present study 62.8% of mothers had given colostrum to their babies whereas 35.5% of mothers had discarded colostrum the findings were similar to the study conducted by Davara et al where 68.5% of mothers had given colostrum to their infants. 18 16.5% of mothers in present study were using the bottle to feed their children these findings were comparable (13.3%) to the study conducted by Varshney et al 19 At 6 months of age, energy and nutrient requirement of the child increases which cannot be fulfilled only by breast milk, thus introduction of complementary foods are mandatory to meet the energy requirement of a growing child and if complementary foods are not introduced at this period of life growth of the infants may be falter.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study 38.8% of children had received prelactial feeds, Similar findings were reported in studies conducted by Manasa et al, Srividya et al and Kumar et al [11][12][13] A study done by Nethra et al in the same area reported a low (18%) prevalence of pre lacteal feeding practice among mothers. 14 The probable discordance with above study may be possibly due to inclusion of rural and urban mothers in our study A study done by Saravanan et al 15 In the same region among rural mothers reported a higher (60.2%) prevalence of pre lacteal feeding practice among mothers.…”
Section: Discussionsupporting
confidence: 90%
“…In our study 90% of mothers are against prelacteal feeds (Table 2) compared to only 68% are against prelacteal feeds in other district of Karnataka. 8 Mothers intend to Wean infants after 6 months is 62.9% whereas 21.2% wants to wean their infants after 3 months in our study. Whereas weaning is 86.5% after 6 months and 13.5% after 3 months in Upadhye JV et al 9 There is a estimation of 1.4million deaths and 10% of the disease burden in less than 5 years of age is found in children with sub optimal breast feeding and exclusive breast feeding less than 6 months of age.…”
Section: Resultsmentioning
confidence: 57%